Stellar laboratories: VIII. New Zr IV - VII, Xe IV - V, and Xe VII oscillator strengths and the Al, Zr, and Xe abundances in the hot white dwarfs G191-B2B and RE0503-289 - Rauch, Thomas; Demleitner, Markus (Astronomy and astrophysics, 2017)
Context. For the spectral analysis of high-resolution and high-signal-to-noise spectra of hot stars, state-of-the-art non-local thermodynamic equilibrium (NLTE) model atmospheres are mandatory. These are strongly dependent on the reliability of the atomic data that is used for their calculation. Aims. To search for zirconium and xenon lines in the ultraviolet (UV) spectra of G191−B2B and RE 0503−289, new Zr iv-vii, Xe iv-v, and Xe vii oscillator strengths were calculated. This allows, for the first time, determination of the Zr abundance in white dwarf (WD) stars and improvement of the Xe abundance determinations. Methods. We calculated Zr iv-vii, Xe iv-v, and Xe vii oscillator strengths to consider radiative and collisional bound-bound transitions of Zr and Xe in our NLTE stellar-atmosphere models for the analysis of their lines exhibited in UV observations of the hot WDs G191−B2B and RE 0503−289. Results. We identified one new Zr iv, 14 new Zr v, and ten new Zr vi lines in the spectrum of RE 0503−289. Zr was detected for the first time in a WD. We measured a Zr abundance of −3.5 ± 0.2 (logarithmic mass fraction, approx. 11 500 times solar). We identified five new Xe vi lines and determined a Xe abundance of −3.9 ± 0.2 (approx. 7500 times solar). We determined a preliminary photospheric Al abundance of −4.3 ± 0.2 (solar) in RE 0503−289. In the spectra of G191−B2B, no Zr line was identified. The strongest Zr iv line (1598.948 Å) in our model gave an upper limit of −5.6 ± 0.3 (approx. 100 times solar). No Xe line was identified in the UV spectrum of G191−B2B and we confirmed the previously determined upper limit of −6.8 ± 0.3 (ten times solar). Conclusions. Precise measurements and calculations of atomic data are a prerequisite for advanced NLTE stellar-atmosphere modeling. Observed Zr iv-vi and Xe vi-vii line profiles in the UV spectrum of RE 0503−289 were simultaneously well reproduced with our newly calculated oscillator strengths.